Thyroid hormones and ovarian reserve: a comprehensive study of women seeking infertility care - Muge Halici; Mustafa Ege Seker; Irem Yagmur Gebedek; Merve Nida Gokbak; Abdurrahman Furkan Cetisli; Ahmet Berkan Ciftci; Emine Konac; Sule Yildirim Kopuk; Bulent Tiras; Yigit Cakiroglu (BMC, 2023)
Abstract Background Ovarian reserve is the number of oocytes remaining in the ovary and is one of the most important aspects of a woman's reproductive potential. Research on the association between thyroid dysfunction and ovarian reserve has yielded controversial results. In our study, we aimed to investigate the relationship between thyroid-stimulating hormone (TSH) levels and ovarian reserve markers. Methods From 1443 women seeking infertility care, the data of 1396 women aged between 20-45 years old who had a body mass index between 18-30 kg/m2 were recruited for this retrospective study. The anti-Müllerian hormone (AMH) and TSH relationship was analyzed with generalized linear and polynomial regression. Results Median age, follicle-stimulating hormone (FSH), AMH, and TSH levels were 36.79 years, 9.55 IU/L, 3.57 pmol/L, and 1.80 mIU/L, respectively. Differences between TSH groups were statistically significant in terms of AMH level, antral follicle count (AFC), and age (p = 0.007 and p = 0.038, respectively). A generalized linear regression model could not explain age-matched TSH levels concerning AMH levels (p > 0.05). TSH levels were utilized in polynomial regression models of AMH, and the 2nd degree was found to have the best fit. The inflection point of the model was 2.88 mIU/L. Conclusions Our study shows a correlation between TSH and AMH values in a population of infertile women. Our results are as follows: a TSH value of 2.88 mIU/L yields the highest AMH result. It was also found that AMH and AFC were positively correlated, while AMH and FSH were negatively correlated.